(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
The advent of Hinduism and Buddhism in Nusantara in the seventh century until the fourteenth century ushered in a period of great influence by Hinduism-Buddhism ideology in the Malay world. These two religious beliefs had left a cultural impact which changed the values and worldview of the Malays who practiced animism and ancestral religion before the advent of Islam. Therefore, this study aims to analyze the symbolism of devarāja (god-king) which manifested through the practice of cult in the Malay society and to a certain extent is reflected in classical Malay literary works. The data collection was made using primary sources such as Hikayat Banjar, Hikayat Parang Puting, Hikayat Sang Boma, Hikayat Panji Semirang and Hikayat Malim Deman. The choice of these classical literatures was considered as neutral due to the classics belonging to different genres, such as historical texts, Panji tales, Hindu based literature, Islamic transition texts. The results of this study demonstrate the different styles of writing that had been used to highlight the symbolism of devarāja (god-king) in order to highlight the sovereignty of the Malay rulers. Keywords: spiritualism, god, symbolism, devaraja, classical literature, Hindu-Buddha, universal outlook, sovereignty of Malay rulers